“Sì in muran come fuora de muran”: transcultural itineraries and material counternarratives in venetian glass, c. 1450-1650 - Hyatt, Emily (The journal of transcultural studies, 2021)
Few early modern materials are linked quite as closely to their site of primary production as Venetian glass. In the period between 1450 and 1650 CE, beginning with the emergence of the highly limpid and colorless vetro cristallo, glass made both in Venice and à la façon de Venise gained international acclaim, and cloaked Murano’s workshops and workers in artisanal myth. Although recent studies have examined the significance of this material for Venice and Murano, less is known about the processes through which this material became “Venetian.” This article proposes a transcultural interpretive framework that identifies and de-naturalizes this process of venezianizzazione (Venetianization) by focusing on the itineraries of the raw materials essential to the making of Venetian glass. By tracing the complex itineraries of matter such as Syrian plant ash and silica-rich stones from the Ticino river, it asks how, at which moment, and through whom such materials gained a relationship with Venice, and whether their prior uses, histories, and associations were erased in the furnaces of Murano’s workshops.